Isolamento de microrganismos e seleção de enzimas microbianas com aplicações biotecnológicas no tratamento de esgotos - Susanne Facchin (2013)
The main organic contaminants in municipal wastewater are proteins, polysaccharides, and lipids, which must be hydrolyzed to smaller units. A high concentration of oil and grease in wastewater affects biological wastewater treatment processes by forming a layer on the water surface, which decreased the oxygen transfer rate into the aerobic process. Microbial proteases, lipases, amylases, and celullases should play essential roles in the biological wastewater treatment process. The present study aimed to isolate lipase- and other hydrolytic enzyme-producing microorganisms and assess their degradation capabilities of fat and oil wastewater in the laboratory. We also evaluated microbial interactions as an approach to enhance lipolytic activity. We place emphasis on lipase activity because oil and grease are not only environmental pollutants, but also form an undesirable tough crust on pipes of sewage treatment plants. Thirty-five lipolytic microorganisms from sewage were identified and assessed for hydrolytic enzyme profiles. Lipases were characterized in detail by quantification, chain length affinity, and optimal conditions for activity. The good stability of isolated lipases in the presence of chemical agents, thermal stability, wide range of pH activity and tolerance, and affinity for different lengths of ester chains indicates that some of these enzymes may be good candidates for the hydrolysis of organic compounds present in wastewater. A combination of enzymes and fermenting bacteria may facilitate the complete hydrolysis of triglycerides, proteins, and lignocellulose that normally occur in the wastes of industrial processes.